2021
DOI: 10.1116/6.0001124
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interactions with polystyrene nanoplastics—The role of particle size and protein corona

Abstract: Plastic waste is ubiquitously spread across the world and its smaller analogs-microplastics and nanoplastics-raise particular health concerns. While biological impacts of microplastics and nanoplastics have been actively studied, the chemical and biological bases for the adverse effects are sought after. This work explores contributory factors by combining results from in vitro and model mammalian membrane experimentation to assess the outcome of cell/nanoplastic interactions in molecular detail, inspecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…These results are contrary to the results from Kihara et al, where precoated PS NPs (20 nm) decreased cytotoxic effects in A549 cells, independent from the type of protein corona (positive lysozymes or negatively charged human serum albumin proteins). [154] However, this is in line what is observed from C. elegans experiments comparing particle effect with and without eco-corona. [155] As already mentioned in Chapter 3, an ecocorona is encapsulating the particles through the association of organic molecules in the environment, like dissolved organic matter.…”
Section: Lack Of Information About Np Environmental Conditionssupporting
confidence: 85%
“…These results are contrary to the results from Kihara et al, where precoated PS NPs (20 nm) decreased cytotoxic effects in A549 cells, independent from the type of protein corona (positive lysozymes or negatively charged human serum albumin proteins). [154] However, this is in line what is observed from C. elegans experiments comparing particle effect with and without eco-corona. [155] As already mentioned in Chapter 3, an ecocorona is encapsulating the particles through the association of organic molecules in the environment, like dissolved organic matter.…”
Section: Lack Of Information About Np Environmental Conditionssupporting
confidence: 85%
“…The length and fragment content of the tail is proportionate to the degree of DNA damage. Su ciently small PS can make a direct contact with the nuclear membrane, which can damage DNA and disturb DNA replication [53]. Moreover, indirectly, DNA damage caused by the large amount of cytoplasmic ROS generated by PS through oxidative stress [54].…”
Section: Comet Assaymentioning
confidence: 99%
“…So far, protein corona formation has been mainly investigated in the case of nanoparticles (i.e., diameter < 0.1 μm 24 ). 14,16,19,23,25,26 Besides particle size, 27,28 surface modifications like carboxy or amine groups influence protein corona formation and composition. 14,16,29−31 Noteworthy, it has been shown that protein corona composition can influence the cellular uptake of particles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In particular, protein–protein interactions play a more important role than those described by Vroman. , Hence, it can be stated that the mechanism of protein corona formation is still not fully understood. So far, protein corona formation has been mainly investigated in the case of nanoparticles (i.e., diameter < 0.1 μm). ,,,,, Besides particle size, , surface modifications like carboxy or amine groups influence protein corona formation and composition. ,, Noteworthy, it has been shown that protein corona composition can influence the cellular uptake of particles. In the case of a protein corona containing immunoglobulins and complement factors from human plasma on pristine particles, a stealth effect was observed where cells did not recognize the particles anymore, but this is dependent on cell type.…”
Section: Introductionmentioning
confidence: 99%